Mouse characteristics that affect establishing xenografts from hepatocellular carcinoma patient biopsies in the United States. (24th December 2021) - Zou, Chenhui; El Dika, Imane; Vercauteren, Koen O. A.; Capanu, Marinela; Chou, Joanne; Shia, Jinru; Pilet, Jill; Quirk, Corrine; Lalazar, Gadi; Andrus, Linda; Kabbani, Mohammad; Yaqubie, Amin; et al.
Abstract: Background: Hepatocellular carcinoma (HCC) patient‐derived xenograft (PDX) models hold potential to advance knowledge in HCC biology to help improve systemic therapies. Beside hepatitis B virus‐associated tumors, HCC is poorly established in PDX. Methods: PDX formation from fresh HCC biopsies were obtained and implanted intrahepatically or in subrenal capsule (SRC). Mouse liver injury was induced in immunodeficient  Fah −/−  mice through cycling off nitisinone after HCC biopsy implantation, versus continuous nitisinone as non‐liver injury controls. Mice with macroscopically detectable PDX showed rising human alpha1‐antitrypsin (hAAT) serum levels,  and conversely,  no PDX was observed in mice with undetectable hAAT. Results: Using rising hAAT as a marker for PDX formation,  20 PDX were established out of 45 HCC biopsy specimens (44%) reflecting the four major HCC etiologies most commonly identified at Memorial SloanKettering similar to many other institutions in the United States. PDX was established only in severely immunodeficient mice lacking lymphocytes and NK cells. Implantation under the renal capsule improved PDX formation two‐fold compared to intrahepatic implantation. Two out of 18 biopsies required murine liver injury to establish PDX,  one associated with hepatitis C virus and one with alcoholic liver disease. PDX tumors were histologically comparable to biopsy specimens and 75% of PDX lines could be passaged. Conclusions: Using cycling off nitisinone‐induced liver injury,  HCC biopsies implanted under the renal capsule of severely immunodeficient mice formed PDX with 57% efficiency as determined by rising hAAT levels. These findings facilitate a more efficient make‐up of PDX for research into subset‐specific HCC. Abstract : The establishment of PDX xenograft models in Hepatocellular carcinoma (HCC) may depend on mouse liver injury. Inducing chronic liver injury in immunodeficient  Fah −/−  mice through cycling off nitisinone after HCC biopsy implantation, helped produce PDX with 57% efficiency as determined by rising human alpha1‐antitrypsin (hAAT) serum levels.